A model for evaluating the paradoxical impacts of organizational members' social use of SNSs on destructive voice. Issue 3 (30th January 2019) - Tabarsa, Gholam ali; Olfat, Mohammad; Shokouhyar, Sajjad
Abstract : Purpose: This study aims to investigate the influence of organizational members' social use of social networking sites (SNSs) on employees' destructive voice directly and considering the mediating role of job satisfaction and affective commitment to the organization. Design/methodology/approach: In total, 240 employees of Asia-tech Company have participated in this study. To test the hypotheses, the researchers have used the partial least squares (PLS) method with the help of smart PLS software (version 2.0). Findings: The results showed that organizational members' social use of SNSs has a positive effect on destructive voice directly and considering job satisfaction as a mediator. However, social use of SNSs in the workplace considering the mediating role of affective commitment has a negative effect on destructive voice. Practical/implications: The results of the study edify managers on how social use of SNSs in the workplace has paradoxical effects on destructive voice directly and regarding affective commitment as a mediating variable. Thus, the main contribution of this study is the fact that although social use of SNSs has many advantages such as promotion of job satisfaction and affective commitment in the workplace, it might have some detrimental effect such as reinforcement of destructive voice. Originality/value: The model presented in this study is totally unique. Moreover, the investigations showed that there is no documented study regarding the examination of the effect of social use of SNSs on destructive voice directly and considering the mediating role of job satisfaction and affective commitment.